World regional differences in outcomes for patients with peripheral artery disease: Insights from the EUCLID trial - Norgren Lars; North Rebecca; Baumgartner Iris; Berger Jeffrey S; Blomster Juuso I; Hiatt William R; Jones W Schuyler; Katona Brian G; Mahaffey Kenneth W; Mulder Hillary; Patel Manesh R; Rockhold Frank W; et al. (SAGE PUBLICATIONS LTD, 2022)
Regional variations exist in the epidemiology of peripheral artery disease (PAD), in comorbidities, use of secondary prevention, and outcomes. Large studies of these variations in worldwide populations are rare. The EUCLID (Examining Use of tiCagreLor In peripheral artery Disease) trial included 13,885 patients with PAD from four geographical regions (Central/South America, Europe, Asia, North America) and compared monotherapy with ticagrelor and clopidogrel. Inclusion criteria were either an ankle-brachial index < 0.80 or a prior revascularization. The primary efficacy endpoint was time to first occurrence of any event in the composite of cardiovascular death, myocardial infarction, or ischemic stroke and did not differ between the study arms. This post hoc analysis of EUCLID confirmed that regional differences occurred in the inclusion criteria with more prior revascularization in North America (73.9%) and Asia (72.5%) compared with Central/South America (34.0%) and Europe (51.6%). The characteristics of patients also differed. Prior amputation at baseline was most frequent in Central/South America (6.3%) compared with other regions (1.6-2.8%). A history of stroke was most common in Asia, coronary heart disease in North America, and diabetes in Central/South America compared with other regions. The incidence of outcomes in patients with PAD varied by region. North America had the highest rate of the primary combined endpoint (5.97 events/100 patient-years). Corresponding rates were 4.80, 3.95, and 3.87 for Asia, Europe, and Central/South America, respectively. Hospitalization for acute limb ischemia (events/100 patient-years) was most frequent in Europe (0.75) and North America (0.74) compared with Asia (0.60) and Central/South America (0.33). Adjustment for inclusion criteria and relevant PAD characteristics did not have a major impact on these regional differences. Further adjustment for concomitant disease, risk factors, and preventive medication modified the regional differences only marginally. In conclusion, substantial regional differences were found in cardiovascular and limb outcomes in patients with PAD and were not explained by variation in the category of included patients, concomitant disease, risk factors, and prevention. Such differences, which may be due to variation in other factors such as background population rates or clinical care, need to be considered when designing and interpreting large international studies (ClinicalTrials.gov Identifier: NCT01732822).